Metal injection molding (MIM) of nickel-base superalloys - Horke, Katharina; Meyer, Andreas; Singer, R. F. (Handbook of Metal Injection Molding (2nd edition), 2019)
Although the number of commercial applications is still limited, the activities in the field of metal injection molding (MIM) of nickel-base superalloys have been steadily increasing during the last decade. The aerospace industry provides the main driving force behind this development. MIM seems attractive as it offers a high potential in cost reduction. This chapter gives an overview on the current development status for MIM of nickel-base superalloys. Important factors for MIM processing with regard to debinding and sintering as well as achievable properties are summarized. Potential new fields of applications for metal injection molded nickel-base superalloys are discussed.
CRIS-Team WoS Importer:2019-11-08
Keywords: MIM; Superalloys; Nickel-base superalloys; Sintering; Grain size; Impurities; Mechanical properties; Creep; Fatigue